Effects of Aging on the Structure and Expression of NMDA Receptors of Somatostatin Expressing Neurons in the Mouse Hippocampus - Gramuntell, Yaiza; Klimczak, Patrycja; Coviello, Simona; Perez-Rando, Marta; Nacher, Juan (Frontiers in Aging Neuroscience, 2021)
Changes in the physiology, neurochemistry and structure of neurons, particularly of their dendritic spines, are thought to be crucial players in age-related cognitive decline. One of the most studied brain structures affected by aging is the hippocampus, known to be involved in different essential cognitive processes. While the aging-associated quantitative changes in dendritic spines of hippocampal pyramidal cells have already been studied, the relationship between aging and the structural dynamics of hippocampal interneurons remains relatively unknown. Spines are not a frequent feature in cortical inhibitory neurons, but these postsynaptic structures are abundant in a subpopulation of somatostatin expressing interneurons, particularly in oriens-lacunosum moleculare (O-LM) cells in the hippocampal CA1. Previous studies from our laboratory have shown that the spines of these interneurons are highly plastic and influenced by NMDA receptor manipulation. Thus, in the present study, we have investigated the impact of aging on this interneuronal subpopulation. The analyses were performed in 3-, 9-, and 16-month-old GIN mice, a strain in which somatostatin positive interneurons express GFP. We studied the changes in the density of dendritic spines, en passant boutons, and the expression of NMDA receptors (GluN1 and GluN2B) using confocal microscopy and image analysis. We observed a significant decrease in dendritic spine density in 9-month-old animals when compared with 3-month-old animals. We also observed a decrease in the expression of the GluN2B subunit in O-LM cells, but not of that of GluN1, during aging. These results will constitute the basis for more advanced studies of the structure and connectivity of interneurons during aging and their contribution to cognitive decline.